Bronchoalveolar lavage with diluited surfactant in children with severe ARDS - Tortolo, L. (Acta Biomedica Atenei Parmensis, 2012)
Acute respiratory distress syndrome (ARDS) is characterised by damage to the arteriolar-capillary endothelium and alveolar epithelium that leads to surfactant deficiency and atelectasis. Alveolar collapse and pulmonary oedema will further induce surfactant inactivation. Surfactant supplementation has been suggested but the treatment is unpredictable. Poor response may be due to inhibition of administered surfactant by plasma components filling the alveolar space, severity of lung injury, time of surfactant application and inadequate dose.We reported the course of gas exchange and pulmonary mechanics after instillation of surfactant in 14 children (3 months-7 years) with severe ARDS, defined as an OI > 30 and a PaO2/FiO2 200 for more than 12 hours. Diluited surfactant lungs lavages were able to increase blood gas exchange in all our patients despite a previous severe gas exchange impairement.